Komparasi Kalender Jawa Islam dan Hijriyah (Analisis Kalender berbasis Lunar Sistem) - Muthi’ah Hijriyati (Menara Tebuireng, 2017)
The calendar system is the important thing for human’s life to know the time and this calculation. Nowadays, calendar in the world based on movement from the Sun (solar system) or Moon (lunar system). Especially in Islamic (Hijriyah) and Javanese calendar, altought both of them based on lunar system, in application they have different rules. We can’t say that 1 Ramadhan is always same with 1 Poso or 1 Dhulhijjah is certainly 1 Besar. To know beginning of the month in Islamic calendar need the astronomical data, that is position of Moon and Sun when conjunction, the height of two object and others. Its mean, need calculation (hisab) or observe (ru’yah) to know that. But in Javanese, the date is always same. 29 days in even months and 30 days in odd months. So that, it can be important cause Hijriyah need to worship for Islamic people and Javanese close to culture and social calendar in Java community in Indonesia